Upaya Penurunan Volume Cairan Pada Pasien Gagal Ginjal Kronis - Faruq, Muhammad Hanif; , Arina Maliya, S.Kep., M.Si.Med (2017)
The number of chronic kidney disease is pretty high in indonesia nowadays. Kidney failure is a dangerous disease if not dealt immediately. Chronic renal failure is usually appears with excess fluid volume that can affect patient's life quality. One of symptoms that appears in this case is edema. When excess fluid happened and edema arises then it has to be dealt quickly and pricesely. Improper handling, in this case, may affect the continuity of patient's life. Therefore, efforts to decrease the excess fluid volume in order to prevent patients undergoing hemodialysis is necessary. The purpose of this research is describing efforts of decreasing excess fluid volume on patients with chronic renal failure in the new wards at muhammadiyah hospital of delanggu. The method that used is descriptive method with case study approach, in the new ward at muhammadiyah hospital of delanggu on 20 march-22 march 2017. The data was submitted through observation, family or patient's interview, medical records and further study. The author's result obtained efforts of declining excess fluid volume on patients with chronic kidney that are monitor vital signs, monitor inputs and outputs, limit input and output, help patients facing the inconvenience of liquids restrictions, collaborate with doctors for giving drug. Excess fluid volume problem yet unsolved, fluid restriction is more effective to declineb excess fluid volume, and drinking red guava juice 150 cc a day could be used for home-carappears handle discomfort of fluid restrictions. Keywords: edema , chronic renal failure, excess fluid volume.